Energy Economics Concepts, Issues, Markets and Governance - Bhattacharyya, Subhes C.; SpringerLink (Online service) (UK : Springer London Ltd, 2011)
This book provides an updated and expanded overview of basic concepts of energy economics and explains how simple economic tools can be used to analyse contemporary energy issues in the light of recent developments, such as the Paris Agreement, the UN Sustainable Development Goals and new technological developments in the production and use of energy. The new edition is divided into four parts covering concepts, issues, markets, and governance. Although the content has been thoroughly revised and rationalised to reflect the current state of knowledge, it retains the main features of the first edition, namely accessibility, research-informed presentation, and extensive use of charts, tables and worked examples. This easily accessible reference book allows readers to gain the skills required to understand and analyse complex energy issues from an economic perspective. It is a valuable resource for students and researchers in the field of energy economics, as well as interested readers with an interdisciplinary background.
1. Introduction to energy economics -- Part 1: Concepts -- 2. Economic concepts applied to the energy sector -- 3. Energy data and energy balance -- 4. Energy demand analysis -- 5. Energy demand forecasting -- 6. Economic analysis of investments -- 7. Economics of non-renewable energy supply -- 8. Economics of renewable energy supply -- 9. Energy Pricing and taxation -- 10. Economics of environment protection -- Part 2: Issues -- 11. Energy challenges -- 12. Energy and Sustainable Development -- 13. Energy Security Issues -- 14. Impact of price volatility -- 15. Energy Investment issues -- 16. Energy Access -- 17. Pollution control from stationary sources -- 18. Pollution control from mobile sources -- 19. Energy saving and energy efficiency improvements -- Part 3: Markets -- 20. International oil market -- 21. Natural gas market -- 22. Coal market -- 23. Electricity market -- 24. Carbon market -- Part 4: Governance -- 25. Institutional perspectives in energy -- 26. Energy sector regulation -- 27. Reform and restructuring of the energy sector -- 28. Regional energy integration and international cooperation.
Mode of access: World Wide Web.
Keywords: Industrial organization; Energy policy; Energy and state; Organization; Planning; Renewable energy resources; Climate change